Improving Cognitive Domain of Graduate Students on Corpus Linguistics Course through the Implementation of Blended Learning - et.al, Mirsa Umiyati, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Face to face learning method caused the students to be uninterested in class, discouraged, bored, stop trying in accomplishing tasks given (Felder and Silverman, 1988) however blended learning that is prove to be more effective in improving student satisfaction and knowledge (Marchalot et al (2018), Khodeir (2018), Alsalhi et al (2019), Li et a (2019), Yigzaw et al (2019),Yao (2019), Cocquyt et al (2019), Law et al (2019), (Asarta & Schmidt, 2020). This cross-sectional study aims to evaluate the effectiveness of blended learning in improving graduate students cognitive domain until level 5 (synthesis) on corpus linguistic. The population of this study were first grader university students who enrolled in 2018/2019 (group 1) and third grader university students who enrolled in 2019/2020 (group 2) in corpus linguistics course. The data were analysed using the statistical program that available in SPSS. The similarity of the groups was analysed using crosstabulation and Mann Whitney U test. The different mean (average) scores of the two groups were analysed using an unpairing student t-test/ Mann Whitney U test depend on the equality of variant. The results of the testing revealed that the average score achieved by the students using face to face learning methods was 84.4737 while average scores achieved by the students with blended learning was 90.0000. Both scores were highly significant different with p < 0.01. In conclusion, blended learning is more effective compared to face to face learning